2022
DOI: 10.1186/s12891-022-05819-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combined extracorporeal shock-wave therapy and hyaluronic acid injections for patients with shoulder pain due to rotator cuff tendinopathy: a person-centered approach with a focus on gender differences to treatment response

Abstract: Background: Rotator cuff (RC) tendinopathy is a common shoulder pain condition. Extracorporeal shockwave therapy (ESWT) and hyaluronic acid peritendinous injection are viable treatment options for RC tendinopathy.The aim of this study is to evaluate the response in two different therapeutic rehabilitative approaches, the combined treatment ESWT plus hyaluronic acid injections (E + Hy) compared to ESWT alone (ESWT-al), in a cohort of patients with RC tendinopathy according to gender differences.Methods: This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Fourth, the double size of particles (HMW has very good rheological properties due to LMW, which triggers endogenous HA production by stimulation of fibroblasts). Lastly, participants in previous studies showed very good tolerance of the product administered together with PRP and no cytotoxic effect [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, the double size of particles (HMW has very good rheological properties due to LMW, which triggers endogenous HA production by stimulation of fibroblasts). Lastly, participants in previous studies showed very good tolerance of the product administered together with PRP and no cytotoxic effect [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the presence of infection in both group A (with HDFs) and group B (without HDFs) can be considered evidence that it was because of the multiple surgical procedures performed in a stressful environment, rather than an experimental or culture technique of the HDFs. Moreover, as the safety of HDFs and HA has already been proven by numerous clinical studies, 25,33 we assumed that the rabbits’ death was not related to safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sEMG is simple to use, since mDurance provides a step-by-step guide that practically explains and graphically represents on the tablet screen all the procedures, from applying the sensors to reading the final results. Therefore, sEMG could provide the opportunity to improve the effectiveness of home-based shoulder rehabilitation protocols, whose current main limitation is the difficulty of carrying out the exercises correctly, and therefore by the slowness in achieving the relative benefits [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%